The exiles [videorecording (DVD)] - Mackenzie, Kent; Alexie, Sherman, 1966-; Burnett, Charles, 1944-; Williams, Yvonne; Nish, Homer, 1934-1980; Reynolds, Tommy; Rodriguez, Rico; Sam, Clifford Ray (Milestone Film & Video ; Exclusively distributed by Oscilloscope Laboratories, 2009)
"[C]hronicles one night in the lives of young Native American men and women living in the Bunker Hill district of Los Angeles. Based entirely on interviews with the participants and their friends, the film follows a group of exiles -- transplants from Southwest reservations -- as they flirt, drink, party, fight, and dance"--Container.